Management outsourcing business models: A perspective of sustainability - Jerónimo, C.; Pereira, L.; Saraiva, M. (2019 IEEE International Conference on Engineering, Technology and Innovation (ICE/ITMC), 2019)
In a world characterized by intense competition, outsourcing has infiltrated the management world in a major way. Outsourcing services are becoming an increasingly important source to companies focus on their core competencies, reduce costs, and increase efficiency in several organizational functions. Even though outsourcing of business activities has become a prevalent practice amongst organisations, the literature provides only a one-dimensional view of the phenomenon by focusing on the service receivers' perspectives - buyer. This article overcomes this weakness by investigate and analyse the business models of outsourcing companies - vendor - as a way to understand how they reach a sustainable competitive advantage that differentiates them in the market. Hence, the whole investigation explores the service provider's perspectives by conducting interviews to 16 top executives from 15 different outsourcing companies in Portugal. The findings suggest that all the organizations presented in the study face the same challenges/pains in the market and each of them manifest an exclusive combination of mechanisms, methods, strategies and approaches within their business models to be differentiated in the market and sustainable in terms of efficiency and competitive advantage.